Spiritual Nourishment - Linda L. Dunn (Rural Nurse Organization; Binghamton University, 2012)
Spring is one of my favorite seasons of the year. A new beginning, beautifully sculptured lawns, flowers in colorful array, birds singing, juicy berries to delight the palate, and tax refunds ...wow!! Despite the beauty of spring, there are things I don't enjoy, such as pollen, allergy woes, and tornadoes. Such is life. Everyday can be a new beginning with new opportunities; however, it may also bring unexpected adversities. As nurses, we observe patients who may be experiencing more than one stressor. In addition to family crises, many are also experiencing caregiver stress, grief and loss, newly-diagnosed illnesses, not to mention current economic woes. Suddenly that "spring in our step" may be weakened. How can nurses maintain spiritual wellness that will enable us to reach out to help those facing adversity? I have been reading Spirituality: Living Our Connectedness by Burkhardt & Nagai- Jacobson (2002). These authors suggest some timely activities that integrate the beauty of nature and our gorgeous spring season to nurture the spiritual self. They suggest we give ourselves an hour, or even better, one whole day to attend to self. When did you last take a devotional book outside to read or go outside to meditate or journal? Taking a stroll to admire the beauty of nature is not only good for the soul, but great exercise for the body. Plant a garden. Watch a sunrise or a sunset. Run in the rain or just sit still and listen. I know I never take enough time just to be still. Healthcare arenas could take this same idea and provide areas to be quiet at the end of a workday. An outside meditation garden with benches, a fountain, and a bird feeder would be restful. Just close your eyes and picture it - can you hear the flowing water and hear the sweet melodies? A walking trail could actually rejuvenate spiritual energy. However, we need not wait on healthcare environments to take care of our spiritual nurturance. I challenge you to reconnect with nature, the spring season, and the Sacred. The dark winter may have created an emptiness within the spiritual self that requires a "spring" of nourishment.